Pareto Governors for Energy-Optimal Computing - Sen, Rathijit; Wood, David A. (ACM Transactions on Architecture and Code Optimization, 2017)
The original definition of energy-proportional computing does not characterize the energy efficiency of recent reconfigurable computers, resulting in nonintuitive “super-proportional” behavior. This article introduces a new definition of ideal energy-proportional computing, new metrics to quantify computational energy waste, and new SLA-aware OS governors that seek Pareto optimality to achieve power-efficient performance.